Self-Regulated Learning to Reduce Academic Procrastination of Muhammadiyah Boarding School Students at SMP Muhammadiyah 5 Reinforcement - Zaki Nur Fahmawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Academic procrastination is a procrastination behavior characterized by doing unimportant things instead of prioritizing more important tasks or activities. One of the triggers for academic procrastination is low self-regulation in learning. This can be minimized by providing training. The purpose of this research is to look at the effectiveness of self-regulated learning training on student procastination. The training participants were 55 students of SMP Muhammadiyah 5 Reinforcement who took part in the Muhammadiyah Boarding School (MBS) program. Data analysis using paired sample t test. The study used the pre-experimental design method in the form of one group pretest-posttest. The result is that there is a difference between the pretest and posttest of academic procrastination after being given self-regulated learning training, with a large effect of -0.426 which is included in the moderate category. It can be concluded that self-regulated learning training is effective in reducing academic procrastination